Magnetic resonance imaging of the peripheral joints in psoriatic arthritis - M.A. Cimmino; G. Garlaschi; E. Silvestri; M. Parodi; R. Scarpa; M.C. D'Auria (PAGEPress Publications, 2011)
Objective: Magnetic resonance imaging (MRI) has been widely used for the evaluation of rheumatoid arthritis (RA), with only a minority of studies considering other types of arthritis. This review is concerned with an evaluation of the MRI appearance of peripheral joints in psoriatic arthritis (PsA). Methods: A Medline search was performed to identify all publications from the years 1985 to 2006 concerning MRI of the peripheral joints and PsA. Additional papers were retrieved by scanning the references to the Medline-listed articles. Articles written in English, French, German, and Italian were included. Results: Most papers studied the hand and wrist, and only few of them were concerned with the knee, foot, temporomandibular joint, and elbow. Patients with PsA showed often, but not always, a pattern of joint inflammation which extended beyond the capsule into the extraarticular tissue. Bone oedema and erosions were less frequent than in RA. In particular, bone oedema at the entheseal junction was seen, especially in the knee. The degree of synovitis, assessed by dynamic MRI, was similar in PsA and RA. Discussion: Data on MRI of the peripheral joints in PsA are scanty. Only few studies were specifically designed to evaluate the pattern of arthritis in PsA, with most information deriving from papers where different types of arthritis were considered together. An enthesis-related origin of PsA has been proposed in contrast to the primarily synovial inflammation of RA. This pathogenic interpretation is likely to be true, but does not explain all cases of PsA, and needs to be confirmed by further studies.